Design and fabricate a mini bending test machine - Wan Mohd Naim Wan Mohd Yusoff (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
Manufacturing engineering knowledge is very important to carry out this project to ensure that the student understand what they are needed to do. This project is about designing and fabricating a mini testing bending machine that can be used by university student to conduct bending test. This project involved a process of designing bending testing machine with a consideration of a few factors that is the size, cost and portability. To ensure that the design is not the same as the design on the market, studies have been conducted to examine and to compare the design that is already in the market. To fabricate this design, there are using a few machining process such as cutting, milling and welding.